Oxidative nucleation and growth of Janus-type MnOx–Ag and MnOx–AgI nanoparticles. Issue 32 (2nd August 2019) - Zhang, Lei; Jin, Lei; Yang, Yue; Kerns, Peter; Su, Xingsong; Meng, Michael; Liu, Ben; He, Jie
Abstract : We report a novel synthetic method of Janus-type MnO x –Ag and MnO x –AgI nanoparticles based on oxidative nucleation and growth. Abstract : Janus nanoparticles (NPs) containing two chemically distinct materials in one system are of great significance for catalysis in terms of harnessing catalytic synergies that do not exist in either component. We herein present a novel synthetic method of two Janus-type MnO x –Ag and MnO x –AgI NPs. The synthesis of Janus-type MnO x –AgI NPs is based on the oxidative nucleation and growth of Ag domains on MnO first and the subsequent iodization of Ag. A mild and non-disruptive iodization strategy is developed to yield Janus MnO x –AgI NPs, in which converting Ag to AgI domains with iodomethane (CH3 I) is achieved through partial iodization. Simultaneously, Mn 2+ species in the primary MnO octahedra are oxidized during the growth of Ag NPs, leading to the formation of amorphous p-type MnO x domains. Therefore, the as-resultant Janus-type MnO x –AgI NPs combining two semiconductors into an integrated nanostructure can be used as an efficient photocatalyst for visible-light-driven water oxidation. Janus MnO x –AgI NPs show an expected photocatalytic activity even in the absence of Ru(bpy)3 Cl2 as an electron mediator. This intriguing synthesis may offer a new opportunity to develop asymmetric nanostructures of two semiconductors that will potentially be efficient photocatalysts for solar-driven water splitting.